Pengaruh Kecerdasan dan Minat Pribadi Sosial terhadap Penyesuaian Diri Mahasiswa Bimbingan dan Konseling - Sari, Nina Permata; Rachmayanie, Ririanti (Jurnal Kajian Bimbingan dan Konseling, 2019)
The objective of this research is to identify the influence of intelligence and social self interest on the adaptation skill of the department of guidance and counseling students. This quantitative research used the multiple regression analysis. It used purposive total sampling technique, with sample of 38 students of Department of Guidance and Counseling, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat (ULM). The results show that intelligence and social self interest of the department of guidance and counseling students simultaneously influence the adaptation skill of 35.9%, while the remaining 64.1% is influenced by other factors.